2012
DOI: 10.1080/10934529.2012.650583
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in soil and perennial plants in a mining-affected urban area from Northwestern Romania

Abstract: The mercury (Hg) concentrations were evaluated in soils and perennial plants sampled in four districts of Baia Mare city, a historical mining and ore processing center in Northwestern Romania. The results showed that the Hg concentration exceeded the guideline value of 1.0 mg kg(-1) dry weight (dw) established by the Romanian Legislation, in 24 % of the analyzed soil samples, while the median Hg concentration (0.70 mg kg(-1) dw) was lower than the guideline value. However, Hg content in soil was generally high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…As a result, Hg was present at the highest levels relative to the background, and this result is consistent with Marin Senila et al (2012) [55]. Calculation of NIPI values indicated that the northern piedmont is seriously polluted, with the pollution levels of individual river basins in the following order: Qingyang River > Yangyan River > Yukou River > E River.…”
Section: Discussionsupporting
confidence: 87%
“…As a result, Hg was present at the highest levels relative to the background, and this result is consistent with Marin Senila et al (2012) [55]. Calculation of NIPI values indicated that the northern piedmont is seriously polluted, with the pollution levels of individual river basins in the following order: Qingyang River > Yangyan River > Yukou River > E River.…”
Section: Discussionsupporting
confidence: 87%
“…Multivariate statistics can be used to reveal relationships between different parameters of a dataset [40,41].…”
Section: Results Characterization Using Principal Component Analysismentioning
confidence: 99%
“…The toxicity is influenced both by total concentration and by availability of element [ 16 , 17 ]. Consequently, environmental regulations should include along the total elements thresholds, the evaluation of risk exposure to toxic elements in terms of their availability.…”
Section: Introductionmentioning
confidence: 99%